EFFECT OF PLANT GROWTH REGULATORS FOR INDUCTION OF PARTHENOCARPIC FRUIT IN KAKROL (Momordica dioica Roxb.) (Bangladesh Journal of Plant Breeding and Genetics, 2007)
An experiment was conducted to find out the suitable plant growth regulator(s) for inducing parthenocarpic fruit in kakrol (Momordica dioicia Roxb). Four plant growth regulators, viz. NAA and 2, 4-D (Auxins), Fulmet (Cytokinine) and GA3 (Gibberellic acid) were sprayed at three stages (a day before anthesis, at anthesis, a day after anthesis). Out of four growth regulators 2, 4-D and fulmet induced parthenocarpic fruit development. Fruit set percent, final fruit weight, fruit length and fruit diameter varied significantly with different treatment combinations. 2, 4-D at 50 ppm when applied at anthesis showed better performance in inducing parthenocarpy.DOI: http://dx.doi.org/10.3329/bjpbg.v20i2.17030